2021
DOI: 10.1177/14034948211011793
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depressive symptoms of women in the perinatal period during the COVID-19 pandemic: A systematic review and meta-analysis

Abstract: Aims: The prevalence of perinatal anxiety and depressive symptoms have been speculated to increase during an infectious disease outbreak but remains unknown in the context of the COVID-19 situation. Therefore, this review aimed to examine the prevalence of antenatal and postnatal anxiety and depressive symptoms among pregnant women and postpartum mothers during the COVID-19 period. Methods: Six electronic databases were systematically searched for articles from November 2019 to December 2020. Twenty-six observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
56
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 102 publications
11
56
5
Order By: Relevance
“…For countless employees, the transition to working from home was further complicated by ongoing school closures that tasked parents and other primary caregivers with attending to and educating the children within their households while simultaneously managing their professional obligations and other responsibilities in the home (Rollins, 2020). Results from preliminary published studies suggested that the cumulative impact of the stressors related to the accommodations made in response to COVID-19 is consistent with past research indicating that the long-term impacts of quarantine may lead to extended psychological trauma (e.g., Andrade, 2020) as noted by increases in expressed anger (Brooks et al, 2020), depression (Shorey et al, 2021), loneliness (Goncalves et al, 2020), hypervigilance (Pèrez-Fuentez et al, 2020), and heightened risk of suicide (Fitzpatrick et al, 2020).…”
Section: Introductionsupporting
confidence: 77%
“…For countless employees, the transition to working from home was further complicated by ongoing school closures that tasked parents and other primary caregivers with attending to and educating the children within their households while simultaneously managing their professional obligations and other responsibilities in the home (Rollins, 2020). Results from preliminary published studies suggested that the cumulative impact of the stressors related to the accommodations made in response to COVID-19 is consistent with past research indicating that the long-term impacts of quarantine may lead to extended psychological trauma (e.g., Andrade, 2020) as noted by increases in expressed anger (Brooks et al, 2020), depression (Shorey et al, 2021), loneliness (Goncalves et al, 2020), hypervigilance (Pèrez-Fuentez et al, 2020), and heightened risk of suicide (Fitzpatrick et al, 2020).…”
Section: Introductionsupporting
confidence: 77%
“…Changes in daily routine and restrictions in movement, together with the resulting confinement-related stress, financial insecurity, and burden of health concerns, have taken a heavy negative toll [46,47]. One of the most vulnerable groups impacted by these adverse circumstances is perinatal women at risk of PNDS [12,22]. The current study assessed the prevalence of PNDS in the Israeli Arab and Jewish population and the impact of several of its risk factors related to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Other characteristics of the pandemic period, such as loneliness and isolation due to deprivation of social and family support, a reduction in maternity services, the limited availability of medical resources, restricted travel to hospital appointments, financial difficulties, domestic conflicts, and abuse, all of which have increased worldwide, were found to contribute to increasing the incidence of PND symptoms [12,20,21]. Rates of PND during COVID-19 were reported around 31-40% [12,22]. One study conducted in Canada during COVID-19, for example, showed increased PND and anxiety symptoms (37% and 57%, respectively) compared to similar pre-pandemic pregnancy cohorts [23].…”
Section: Introductionmentioning
confidence: 99%
“…[13]. In a recent review by Shorey et al [14], the pooled prevalence of antenatal anxiety and depressive symptoms during COVID-19 period were reported to be high (40% and 27%, respectively), although most of these studies were based in high income countries and Asia. The pandemic and implementation of COVID-19 containment measures will greatly affect perinatal health [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review by Shorey et al [14], the pooled prevalence of antenatal anxiety and depressive symptoms during COVID-19 period were reported to be high (40% and 27%, respectively), although most of these studies were based in high income countries and Asia. The pandemic and implementation of COVID-19 containment measures will greatly affect perinatal health [14][15][16]. For instance, the fear of COVID-19 vertical transmission to unborn babies may affect pregnant women's access to antenatal care, lockdowns and movement restrictions may cut-off access to social support, and physical distancing causing social isolation, which may contribute to elevated stress and anxiety [15,16].…”
Section: Introductionmentioning
confidence: 99%